Clinical Trials and Outcome Measures in Adults With Hearing Loss - Munro, Kevin J.; Whitmer, William M.; Heinrich, Antje (Frontiers in Psychology, 2021)
Clinical trials are designed to evaluate interventions that prevent, diagnose or treat a health condition and provide the evidence base for improving practice in health care. Many health professionals, including those working within or allied to hearing health, are expected to conduct or contribute to clinical trials. Recent systematic reviews of clinical trials reveal a dearth of high quality evidence in almost all areas of hearing health practice. By providing an overview of important steps and considerations concerning the design, analysis and conduct of trials, this article aims to give guidance to hearing health professionals about the key elements that define the quality of a trial. The article starts out by situating clinical trials within the greater scope of clinical evidence, then discusses the elements of a PICO-style research questions. Subsequently, various methodological considerations are discussed including design, randomization, blinding, and outcome measures. Because the literature on outcome measures within hearing health is as confusing as it is voluminous, particular focus is given to discussing how hearing-related outcome measures affect clinical trials. This focus encompasses how the choice of measurement instrument(s) affects interpretation, how the accuracy of a measure can be estimated, how this affects the interpretation of results, and if differences are statistically, perceptually and/or clinically meaningful to the target population, people with hearing loss.